EFFICIENCY OF DOMESTIC SYSTEM OF EMPLOYEES CLAIMS PROTECTION IN EVENT OF AN EMPLOYER BANKRUPTCY - Kovačević, Tijana R (Glasnik Advokatske komore Vojvodine, 2022)
In this paper, the author analyzes ways of protections of employees' claims against employer in bankruptcy proceedings. The first part of the paper discusses various protection modalities that are applied individually or in combination with other means, all with the aim of providing a better safeguard framework for employees involved in bankruptcy proceedings. The central part of the paper is discussing the effectiveness of the domestic system, which is measured by the degree of settlement of claims of employees in bankruptcy proceedings, i.e. the adopted claims before the Solidarity Fund. The paper starts from the assumption that the employee protection system for outstanding claims would be significantly more effective if the employees were more familiar with the functioning of the Solidarity Fund and that the organization of the Fund's functioning is different. In order to achieve the desired goal, it is necessary to place protection in a broader context, which implies the harmony of the institutes of labor and bankruptcy law. As this is not the case in Serbia, the author points to a number of practical problems that arise as a result of this, and which have been identified through an analysis of the work reports of this institution published since its establishment.One of the problems employees and the professional service of the Fund are facing with are unclear legal conditions set for the exercise of rights. In addition to that, potential beneficiaries of the Fund's assets are not adequately familiar with its work, which is a basic prerequisite for the successful exercise of their rights. Confirmation for our stand, we have received in an anonymously conducted internet survey which showed that a vast number of respondents were unaware of the existence of Solidarity Fund. The length of the proceedings before the Fund is not related to the quality of work of the professional service, which has been significantly improved by automatization of the entire procedure, but rather by the insufficient resources of the Fund that are postponing the adoption of the requests. Therefore, it is proposed that encouraging other forms of funding could directly reduce the State's share of the funding and thus ensure better financial stability of the Fund. Finally, on the basis of a critical review of the current regime, it is concluded that the labor-law mechanisms of protection of employees are of limited reach, and that in that regard it should be considered if they could be extended with adequate adjustment to those employers who did not file a formal bankruptcy procedure.